2021
DOI: 10.1057/s41599-021-00781-2
|View full text |Cite
|
Sign up to set email alerts
|

Not-so-straightforward links between believing in COVID-19-related conspiracy theories and engaging in disease-preventive behaviours

Abstract: Since the start of the COVID-19 pandemic, pertinent conspiracy theories have proliferated online, raising the question: How might believing in those conspiracy theories be linked with engagement in disease-preventive behaviours? To answer this, we conducted a repeated cross-sectional survey of around 1500 respondents to examine the link between conspiracy-theory beliefs and disease-preventive behaviours across six time-points in the United States from early February to late March 2020. The findings reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Support and adherence to guidelines also seem to differ between beliefs in different kinds of conspiracy theories ( Farias and Pilati, 2021 ; Oleksy et al, 2021 ; though see Karić and Međedović, 2021 ). Believing in conspiracy theories claiming that the coronavirus SARS-CoV-2 is a hoax or caused by 5G is more negatively related to the adherence to guidelines than believing that the virus is artificially created, potentially as a bioweapon ( Allington et al, 2020 ; Imhoff and Lamberty, 2020 ), which may follow from the fact that the latter conspiracy theories still assume that the virus is dangerous ( Chan et al, 2021 ). The findings that the artificial origin COVID-19 conspiracy belief predicted hygiene but not distancing behaviours ( van Mulukom, 2021 ) and that generic conspiracy ideation is associated with both reduced compliance to distancing guidelines and reduced perceived risk support this idea ( Maftei and Holman, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Support and adherence to guidelines also seem to differ between beliefs in different kinds of conspiracy theories ( Farias and Pilati, 2021 ; Oleksy et al, 2021 ; though see Karić and Međedović, 2021 ). Believing in conspiracy theories claiming that the coronavirus SARS-CoV-2 is a hoax or caused by 5G is more negatively related to the adherence to guidelines than believing that the virus is artificially created, potentially as a bioweapon ( Allington et al, 2020 ; Imhoff and Lamberty, 2020 ), which may follow from the fact that the latter conspiracy theories still assume that the virus is dangerous ( Chan et al, 2021 ). The findings that the artificial origin COVID-19 conspiracy belief predicted hygiene but not distancing behaviours ( van Mulukom, 2021 ) and that generic conspiracy ideation is associated with both reduced compliance to distancing guidelines and reduced perceived risk support this idea ( Maftei and Holman, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the study of conspiracy theories has a long-standing and interdisciplinary tradition [ 1 , 2 , 3 ], uncertainty about their role in people’s health-related responses during the present pandemic remains. Whereas some studies suggest that conspiracy beliefs may undermine the global efforts to contain the virus by reducing people’s adherence to prevention guidelines such as social distancing [ 4 , 5 , 6 ], hygiene [ 5 , 6 ], and vaccination [ 7 , 8 ], other studies fail to replicate these effects [ 9 ] or point toward more complex links [ 10 ]. Thus, an accurate estimate of the overall effect of conspiracy beliefs on health responses across cultures and contexts, including the role of potential moderators, is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, conspiracy beliefs could have significant consequences for the prevention, treatment, and aftermath of disease outbreaks (for reviews, see Douglas, 2021b; van Mulukom et al, 2020). For example, studies have shown that believing COVID-19 is a hoax reduces compliance with disease-prevention measures (e.g., Chan et al, 2021;Imhoff & Lamberty, 2020). Likewise, previous research has also demonstrated the harmful effect of conspiracy beliefs on people's attitudes and plans regarding vaccination (e.g., Hornsey et al, 2018;Jolley & Douglas, 2014).…”
Section: A Brief Overview Of Existing Theoretical Frameworkmentioning
confidence: 99%
“…National collective narcissism is the belief that one's nation is superior and deserving of special treatment, but its exceptionality is insufficiently recognized by others (Golec de Zavala et al, 2009). Wang et al posited that the attribution of responsibility for the COVID-19 outbreak would relate to people's risk-acceptance conspiracy beliefs (i.e., COVID-19 is a real threat and it was intentionally caused by some people, organizations, and countries) and risk-rejection conspiracy beliefs (i.e., the severity of COVID-19 is exaggerated by some people and organizations intentionally; for more on the distinction between the two types of conspiracy beliefs, see Chan et al, 2021). They further posited that the differential attribution of responsibility would mediate the link between national collective narcissism and conspiracy beliefs.…”
Section: The Role Of Personal Narcissism and National Collective Narcissismmentioning
confidence: 99%
See 1 more Smart Citation